Martensitic transformation hysteresis in Ni(Co)-Mn-Sn/MgO metamagnetic shape memory thin films. (November 2018) - Alexandrakis, V.; Aseguinolaza, I.R.; Decker, P.; Salomon, S.; Barandiarán, J.M.; Ludwig, A.; Chernenko, V.A.
Abstract: Hysteresis of martensitic transformations (MTs) is a crucial factor which affects the efficiency and lifetime of actuators and magnetocaloric devices. In the present work we found a tenfold reduction of the thermal hysteresis of MT caused by increasing the MT temperature in a series of Ni(Co)-Mn-Sn thin films deposited onto MgO (001). We have observed that this evolution is accompanied by a drastic change of the temperature dependence of the lattice parameter in the temperature interval of MT. Such a behaviour can be interpreted using the concept of the critical state, where an anhysteretic behaviour is expected. Graphical abstract: Unlabelled Image